Dinamika Konflik Interpersonal Pada Dewasa Awal Dengan Helicopter Parenting - Wahyuningsih, St. Andrifani; Daud, Muh (Universitas Negeri Makassar, 2025)
Helicopter parenting is one of the kinds of patterns of parental care in which parents are involved in the lives of their children often overly. This pattern of caring can lead to interpersonal conflict in children as a result of the negative impact. Especially in early adulthood looking for self-identity. The study responded to as many as two people who were 18-25 years old and felt helicopter parenting. This research uses a qualitative method with a case study approach. The study aims to find out the dynamics of interpersonal conflict in early adulthood with parenting helicopters. Data collection using semi-structured interview techniques that are structured based on domains on parenting helicopters and interpersonal conflicts. Research results on the dynamics of interpersonal conflict in early adulthood with parenting helicopters have shown a range of significant impacts. The positive impact that is felt by the subject in the form of high emotional support. As for the negative impact that the subject feels such as low self-confidence, withdrawal, low life skills, and disruption in the relationship between the child and the parent. The implications of this resear